Estudio comparativo de metodologías de selección de características en sistemas de detección de intrusos (Ids), basado en anomalías de red (2017)
Currently companies do not import their asset classification of asset types of customers, cash, vehicles, accounts receivable, among others, however the most important asset that sometimes passes unbalanced by top management and of the administration of the organizations is THE INFORMATION. The information is very important in a company, so much that the impact that would cause, if the result is a disappeared or worse if it fell into the hands of the competition or of malicious people, is really disastrous, causing serious problems for the management of Organizational processes According to the International Organization for Standardization (ISO) define technological risk [Guidelines for the management of IT security / TEC TR 13335-1] [1996]. For this research, we are going to take into account the risks that are in the moment of safeguarding the information of any company using the technologies of networks of servers and clients, taking into account that the moment of implementing these technologies exist tools that help to safeguard the information, minimizing computer risks and avoiding intrusive access and various typologies of attacks that cause damage to information, network infrastructure and connected equipment. In these situations, there are different types of tools and techniques that protect us and reduce the risk making our company less vulnerable and hardening our network platform. The purpose of this investigation is a selection proposal and the classification of attacks of computer networks supported in systems of detention and prevention of intruders IDS / IPS.